The effect of treaties on foreign direct investment bilateral investment treaties, double taxation treaties and investment flows - Sauvant, Karl P.; Sachs, Lisa E. (Oxford : Oxford University Press, 2009)
In recent years, the treaties and strategies promoting global investment have changed dramatically. This book is a comprehensive assessment of the performance of these treaties. It presents the most recent literature on BITs and DTTs as well as their impact on foreign investments.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Investments, Foreign -- Taxation -- Law and legislation; Double taxation; Treaties